2011
DOI: 10.1074/jbc.m110.215970
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of Cyanobacterial Photosystem II Inhibition by the Herbicide Terbutryn

Abstract: Herbicides that target photosystem II (PSII) compete with the native electron acceptor plastoquinone for binding at the Q B site in the D1 subunit and thus block the electron transfer from Q A to Q B . Here, we present the first crystal structure of PSII with a bound herbicide at a resolution of 3.2 Å . The crystallized PSII core complexes were isolated from the thermophilic cyanobacterium Thermosynechococcus elongatus. The used herbicide terbutryn is found to bind via at least two hydrogen bonds to the Q B si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 52 publications
2
63
0
Order By: Relevance
“…No electron density is observed at the plastoquinone binding site Q C identified previously (Guskov et al, 2009). Two chloride ions near the Mn 4 CaO 5 cluster ( Figure S2a) occupy the positions Cl 1 (Cl 1A in Broser et al, 2011) and Cl 2 (as identified by Umena et al, 2011). No electron density is observed at the Cl 1B position (Broser et al, 2011) and at Cl 3 near PsbU .…”
Section: Cofactors In C 12 E 8 -Dpsiiccmentioning
confidence: 79%
See 2 more Smart Citations
“…No electron density is observed at the plastoquinone binding site Q C identified previously (Guskov et al, 2009). Two chloride ions near the Mn 4 CaO 5 cluster ( Figure S2a) occupy the positions Cl 1 (Cl 1A in Broser et al, 2011) and Cl 2 (as identified by Umena et al, 2011). No electron density is observed at the Cl 1B position (Broser et al, 2011) and at Cl 3 near PsbU .…”
Section: Cofactors In C 12 E 8 -Dpsiiccmentioning
confidence: 79%
“…Two chloride ions near the Mn 4 CaO 5 cluster ( Figure S2a) occupy the positions Cl 1 (Cl 1A in Broser et al, 2011) and Cl 2 (as identified by Umena et al, 2011). No electron density is observed at the Cl 1B position (Broser et al, 2011) and at Cl 3 near PsbU . Three additional Ca 2+ ion positions previously found in the presence of 10 mM CaCl 2 are unoccupied, which is likely due to the absence of calcium in our transformation buffer.…”
Section: Cofactors In C 12 E 8 -Dpsiiccmentioning
confidence: 91%
See 1 more Smart Citation
“…Monosulfuron exhibited its mode of action on acetolactate synthase enzyme in cyanobacteria (Shen et al 2009). Terbutryn was found to bind via two hydrogen bonds to Q B site in the D1 subunit of PS-II in thermophilic cyanobacterium Thermosynechococcus elongatus (Broser et al 2011). The concentration-dependent increase in generation time indicated herbicide affected cell division of Desmonostoc muscorum PUPCCC 405.10.…”
Section: Discussionmentioning
confidence: 98%
“…[3, 4] Computational methods such as ligand-based pharmacophores and quantitative structureactivity relationship (QSAR) are widely used in the discovery of new chemicals for pharmaceutical and agrochemical fields.…”
Section: Introductionmentioning
confidence: 99%